The invention of Shakespeare, and other essays - Orgel, Stephen (University of Pennsylvania Press, 2022)
In The Invention of Shakespeare, and Other Essays Stephen Orgel brings together twelve essays that consider the complex nature of Shakespearean texts, which often include errors or confusions, and the editorial and interpretive strategies for dealing with them in commentary or performance.